Preoperative heart failure in infective endocarditis - Koltunova, G. B.; Senko, O. G.; Khoroshyak, V. Y.; Krikunov, O. A.; Malysheva, T. A.; Spysarenko, S. P. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Heart failure (HF) is the most frequent and most severe complication of infective endocarditis (IE), which rates from 42% to 60% of cases of native IE. Objectives:to review diagnostic criteria and terms of surgical intervention in IE, complicated by HF. Preoperative HF in patients with IE indicates damage of the myocardium and vascular bed with subsequent inability of the cardiovascular system to meet the needs of the patient’s body. Myocardial dysfunction in IE is a complex entity due to the dynamic adaptation of the cardiovascular system to the disease process, the host response, and the effects of medical therapy. Not only myocardial depression leads to the development of HF in patients with IE, but valve structures impairment as well. HF is mainly caused by new or worsening severe aortic or mitral regurgitation, although intracardiac fistulae and, more rarely, valve obstruction may also lead to HF. Presentation of preoperative HF includes clinical and laboratory parameters (New York Heart Association class). Echocardiographic data is of crucial importance for initial evaluation and follow-up. HF in patients with IE causes administration of inotropic support before surgical intervention, greatly complicates intraoperative management and bypass weaning, requires high-doses inotropic support upon admission to the postoperative intensive care unit. This leads to depletion of compromised myocardium and adversely affects the results of surgery. Preoperative HF is an important factor in the international anesthetic and cardiac surgical risk scales (EUROSCORE, APACHE, APACHE II), which significantly impairs the results of treatment. A series of studies revealed reduction in hospital mortality after cardiac surgery in patients with IE, complicated by heart failure, that was reflected in international recommendations on indications and terms of surgical correction in IE. Preoperative HF is the most important predictor of hospital, 6-month and 1-year mortality. Conclusions. Patients with IE share a special part in the spectrum of cardiac surgery community. Such patients need both timely diagnosis of IE, complicated with HF, and, most importantly, timely surgical intervention. HF is principal indication for urgent surgical intervention in patients with IE. The peculiarities of this pathology include not only the quickness of development and the extent of intracardiac impairment, but also the negative influence of the infective process on the myocardium. Combination of these factors leads to development of preoperative HF, which negatively affects the immediate and long-term results of surgical treatment of infective endocarditis.